Transfer of a unit of good between agents in cases of degressively proportional allocation - Łyko, Janusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
The paper discusses the conditions of transferring one unit of a good between agents so as to satisfy the principle of degressively proportional allocation. Solving this problem is a prerequisite for possible modifications of some proportional division methods if we want to apply them in the degressively proportional allocation of goods. In particular, these methods use the relation of priority and are based on the minimization of certain measures of disproportionateness. It turns out that the well-established approaches to proportional allocation are not always possible. The research findings presented in the paper demonstrate that the strongest constraint in this problem is the potential small diversification of the sequence of claims of individual agents
Mathematical Economics, 2016, Nr 12 (19), s. 31-38
Keywords: degressive proportionality; fair division; European Parliament; voting